Antibacterial Activities and Phytochemical of Traditional Thai Medicines: Ya That Bun Job and Ya Learng Pid Samud Formula - Manok, Khemika Kieng Na Fah; Jaengklang, Charinan; Kanantai, Kannika; Phianchring, Maliwan (KKU Science Journal, 2023)
Ya That Bun Job and Ya Learng Pid Samud formula are traditional Thai medicines listed in the National List of Essential Medicine (NLEM). They are used to treat the non-infection diarrhea in Thai folk medicine. In this research, we investigated their anti-bacterial activities using disc diffusion method and determined the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) through the broth microdilution method. Additionally, we compared the total phenolic, total flavonoid and total tannin using spectroscopies technique. Extraction was preformed with three solvents: water, kasaiya water from pomegranate peel and 95% ethanol. The results indicated that the ethanol extract from Ya Learng Pid Samud and the kasaiya water extract of Ya That Bun Job exhibited the highest anti-bacterial activities, with MIC values of 3.91 to 31.25 and 15.62 to 31.25 mg/ml against all E. coli strains, respectively. However, the ethanol extract from Ya That Bun Job showed the highest kill bactericidal activities, with MBC values of 31.25 mg/ml against Enteroaggregative E. coli DMST 26453 (EAEC). In terms of phytochemical analysis, The ethanol extract of Ya Learng Pid Samud displayed a high total phenolic content (294.43 1.77 mg GAE/mg) and total tannin content (159.79 7.29 mg TAE/mg), while, kasaiya water extract of Ya That Bun Job showed a high total flavonoid content (13.43 0.14 mg QE/mg) and total tannin content (182.52 39.32 mg TAE/mg). These finding support the potential of Ya That Bun Job and Ya Learng Pid Samud formula to inhibit certain intestinal pathogenic bacteria within the E. coli family, Which are known to cause diarrhea. The study highlights the traditional Thai treatment of diarrhea using acidic and astringent herbal ingredients and suggests the need for further preclinical studies to validates these observations.